2010
DOI: 10.1016/j.ghir.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone status predicts left ventricular mass in patients after cure of acromegaly

Abstract: Context Growth hormone excess and growth hormone deficiency (GHD) are both associated with increased cardiovascular morbidity. A specific acromegaly-related cardiomyopathy has been described, characterized in part by increased left ventricular mass (LVM). Growth hormone deficiency is associated with reduced LVM. Following cure of acromegaly with surgery or radiation therapy, GHD may develop; however, its effects on cardiac morphology and function in this population are not established. Objective We hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The trial is registered at ClinicalTrials.gov, number NCT00182091. Clinical characteristics, body composition and cardiovascular risk results on a subset of the GHD group have been previously published as baseline results of a longitudinal study, clinical characteristics of a subset of the GHD and GHS groups have been previously published, and echocardiographic measurements on a subset of the three groups have also been previously published; but no body composition or cardiovascular risk marker data have been previously published for the GHS or AA groups.…”
Section: Methodsmentioning
confidence: 99%
“…The trial is registered at ClinicalTrials.gov, number NCT00182091. Clinical characteristics, body composition and cardiovascular risk results on a subset of the GHD group have been previously published as baseline results of a longitudinal study, clinical characteristics of a subset of the GHD and GHS groups have been previously published, and echocardiographic measurements on a subset of the three groups have also been previously published; but no body composition or cardiovascular risk marker data have been previously published for the GHS or AA groups.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the acromegaly-related cardiac abnormalities could worsen after the development of GHD [101]. However, clinical studies do not fully confirm these theoretical hypotheses, as they found a BMI slightly increased [102][103][104] or, even, similar [105][106][107][108] in acroGHD compared to GHD and acromegalic populations. At the same time, while one work reported that acroGHD patients were more hypertensive, dyslipidemic, and diabetic than GHD subjects [109], other Authors pointed out a comparable prevalence of glucose abnormalities and dyslipidemia, as well as a similar amount of body fat and lean mass between acroGHD and refcerebrovascular [5, [82][83][84][85][86][87].…”
Section: B Ghd After Treatment Of Acromegaly (Acroghd)mentioning
confidence: 99%
“…We have previously shown that individuals with a history of acromegaly who develop GHD have normal, not reduced, left ventricular mass corrected for body surface area (LVM/BSA) whereas more than 50% of individuals with a history of acromegaly and GH sufficiency have elevated LVM/BSA [37]. Therefore whether treatment with GH is safe in patients with acroGHD in regard to cardiovascular risk remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%